Correlation of Arm Muscle Power and Abdominal Muscle Strength with Badminton Smash Ability - Marsuna, Marsuna; Rusli, Muhammad; Jud, Jud; Asshagab, Muhtar (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2024)
The research aims to determine the correlation between arm muscle strength and abdominal muscle strength with badminton smash ability. This research was carried out at SMP Negeri 49 South Konawe utilizing the descriptive method with a correlational design. The sampling technique uses a total sampling of 30 junior high students who actively participated in extracurricular activities. The instrument for measuring arm muscle power employs the overhead medicine ball throw test to measure abdominal muscle strength using the sit-up test, while to measure smash ability uses the badminton smash ability test. Data analysis techniques utilize descriptive analysis, regression analysis with normality, linearity tests, and hypothesis testing using the SPSS version 26 application. The correlation results show a significant relationship between variables X1, X2, and Y with a correlation coefficient 0.788. Meanwhile, the contribution coefficient of determination is 0.621, or in other words, 62.1% can contribute to variables X1, durability. From the research results, the greater the arm and abdominal muscle strength a person has, the better their ability to smash in badminton.